2018
DOI: 10.3892/ol.2018.8521
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of growth hormone receptor by Somavert reduces expression of GPER and prevents growth stimulation of triple‑negative breast cancer by 17β‑estradiol

Abstract: Abstract. Currently, conventional chemotherapy is the only treatment option for triple-negative breast cancers (TNBC) due to a lack of a unique target. In TNBC, a high expression of the membrane bound G protein-coupled estrogen receptor (GPER), correlates with a worse outcome. There is a potential for an association between growth hormone receptor (GHR) and GPER expression. To confirm this hypothesis, GHR was inhibited in TNBC cells with Somavert, and GPER expression levels, and the effect on signal transducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Thus, it is important to investigate the effects of E2-GPER signaling on the proliferation, invasion and migration of breast cancer cells. A previous study reported that GPER expression is upregulated in patients with breast cancer ( 54 ). Another study indicated that E2-treated cancer-associated fibroblasts exhibit a positive feedback behavior, which involves GPER/EGFR/ERK signaling and E2 production, and contributes to the progression of breast cancer ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is important to investigate the effects of E2-GPER signaling on the proliferation, invasion and migration of breast cancer cells. A previous study reported that GPER expression is upregulated in patients with breast cancer ( 54 ). Another study indicated that E2-treated cancer-associated fibroblasts exhibit a positive feedback behavior, which involves GPER/EGFR/ERK signaling and E2 production, and contributes to the progression of breast cancer ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, absence of GPER does not affect early tumor initiation or proliferation (30). GPER inhibitors, such as estriol (31) and gefitinib (32), and inhibition of GPER expression by inhibition of growth hormone receptor (33) prevent the 17β-estradiol-induced growth of TNBC. Furthermore, knockdown of ER-α36, which is induced by GPER, reduces estrogen resistance, proliferation, migration and invasion in breast cancer (28).…”
Section: Gper In Breast Cancermentioning
confidence: 99%
“…3 , genes in this triplet are involved in the cancer’s progression via "response to estradiol" biological process. It was also demonstrated that estrogens, like estradiol, are a major factor in the cancer’s progression, like breast cancer [ 68 ]. Additionally, these are tightly linked to the growth hormone (Gh/Gh1) [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was also demonstrated that estrogens, like estradiol, are a major factor in the cancer’s progression, like breast cancer [ 68 ]. Additionally, these are tightly linked to the growth hormone (Gh/Gh1) [ 68 ].…”
Section: Discussionmentioning
confidence: 99%